ANALISIS RATIO KEUANGAN UNTUK MEMPREDIKSI KEGAGALAN BISNIS USAHA KECIL, DAN MENENGAH - Nekhasius Agus Sunarjanto; Herlina Yoka Roida; Agnes Utari Widyaningdyah (Jurnal Bisnis dan Ekonomi, 2016)
This study objective to analyze the financial ratios to predict business failure in small and medium enterprises (SMEs). The data used is the financial data of SME 2009-2015. Data analysis technique used is the binomial logistic regression. The results reveal that the model is fit and ratios that can be used to predict the business failure is working capital ratios: working capital / total assets, current assets / current liabilities, and quick / Inventory. These ratios are working capital ratios, so that SMEs need better management of the working capital. Keywords : Business failure, financial ratio, discriminant binomial logistic analysis.